2018
DOI: 10.1016/j.neuron.2018.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Mettl14 Is Essential for Epitranscriptomic Regulation of Striatal Function and Learning

Abstract: N-methyladenosine (mA) regulates mRNA metabolism and translation, serving as an important source of post-transcriptional regulation. To date, the functional consequences of mA deficiency within the adult brain have not been determined. To achieve mA deficiency, we deleted Mettl14, an essential component of the mA methyltransferase complex, in two related yet discrete mouse neuronal populations: striatonigral and striatopallidal. Mettl14 deletion reduced striatal mA levels without altering cell numbers or morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
112
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(121 citation statements)
references
References 33 publications
(43 reference statements)
8
112
0
1
Order By: Relevance
“…We found that m 6 A mRNA modifications were mainly enriched in the CDS, near the stop codon, and in the 3 UTR, which is similar to the observed topological pattern of m 6 A methylation in mammals [23,34] and rice [28]. However, m 6 A modifications were also enriched near the start codons of Arabidopsis [25].…”
Section: Discussionsupporting
confidence: 82%
“…We found that m 6 A mRNA modifications were mainly enriched in the CDS, near the stop codon, and in the 3 UTR, which is similar to the observed topological pattern of m 6 A methylation in mammals [23,34] and rice [28]. However, m 6 A modifications were also enriched near the start codons of Arabidopsis [25].…”
Section: Discussionsupporting
confidence: 82%
“…17 Due to the important roles in the regulation of m 6 A modification, these methyltransferases and demethylases are also essential for many biological processes. 29 Furthermore, FTO in adult brain is important for fear memory and synaptic plasticity. 28 Deletion of METTL14 profoundly impaired striatal-mediated behaviors in adult mice.…”
Section: Discussionmentioning
confidence: 99%
“…METTL14 is critical for striatum function and transcriptional regulation of learning epitopes. In cell experiments, the deletion of METTL14 reduces striatum m 6 A levels without altering cell number or morphology, increases neuronal excitability and severely impaired striatal-mediated behavior [84].…”
Section: Effect Of M 6 a On Learning And Memorymentioning
confidence: 94%